A note on between-group PCA - Anne-Laure Boulesteix (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2004)
In the context of binary classification with continuous predictors, we proove two properties concerning the connections between Partial Least Squares (PLS) dimension reduction and between-group PCA, and between linear discriminant analysis and between-group PCA. Such methods are of great interest for the analysis of high-dimensional data with continuous predictors, such as microarray gene expression data.
urn:nbn:de:bvb:19-epub-1767-4
Keywords: 519; Classification; dimension reduction; feature extraction; linear discriminant analysis; partial least squares; principal component analysis